First Salmon Covered in Down - G.F. MacDonald Collection (1972)
Salmon covered in eagle down as part of first salmon ceremony. Shot in accordance with Frans Boas's script of the First Salmon Ceremony among the Gitselasu of the Kitselas Canyon. These scenes of resource gathering were initiated in order to fill some of the gaps left by earlier anthropologist and cultural observers among the Gitxsan. Re-enactment of the First Salmon Ceremony performed by the 'Ksan Performing Arts Group. The re-enactment is based on the narrative recorded by Franz Boas for the Gitselesu of Kitselas Canyon.